(untitled) (Journal of Ideas in Health, 2024)
Background: Brucellosis is a contagious bacterial zoonotic disease that is primarily caused by Brucella species. The current study aims to assess knowledge, attitude, and practice towards brucellosis among livestock keepers in Kilosa District-Tanzania. Methods: The cross-sectional study design was employed from February to March 2023 in Kilosa district, Tanzania. A semi-structured questionnaire was employed to evaluate participants’ knowledge, attitudes, and practices related to brucellosis. Collected data were analyzed by using (Microsoft) MS Excel, and the chi-squared test. Results: A total of 150 randomly selected livestock keepers participated in the study, with the majority being male. Participants’ ages ranged from 20 to 70 years. While 138 out of 150 (92%) had heard about brucellosis, only 18 (12%) demonstrated good knowledge of its transmission between livestock and from livestock to humans. Most respondents (80%) were aware of the disease’s clinical signs, identifying abortion in animals and headaches in humans as primary symptoms. Regarding attitudes and practices, 52 (34.7%) strongly agreed that brucellosis is a serious disease in livestock, but only 20 (13%) considered it a significant health threat to humans. Alarmingly, 138 (92%) reported consuming unboiled raw or soured milk. A statistically significant difference was observed in knowledge levels based on sex and education, with a p-value (**p < 0.01) for each variable. These findings highlight gaps in knowledge and risky practices that may contribute to the spread of brucellosis among livestock and humans. Conclusion: This study has shown that there is little understanding and poor attitudes and practices towards brucellosis among livestock keepers in the Kilosa district. This can be addressed by providing community awareness campaigns about zoonotic diseases including brucellosis.